PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PACIFIC EXPRESS CARGO - Ni Komang Alit Vikananda; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Productivity is a measure of the quality and quantity of work that has been done, taking into account the cost of the resources used to do the work. The purpose of this study was to determine the effect of supervision and discipline on the work productivity of employees at PT. Pacific Express Cargo. This research was conducted at PT. Pacific Express Cargo in Denpasar. The number of samples taken as many as 40 employees with saturated sampling method. Data was collected by observation, study of documentation, interviews and distributing questionnaires. The research instrument used is validity test and reliability test. The analysis technique used is the classical assumption test, multiple correlation test, analysis of determination, multiple linear regression analysis, F test and t test. Based on the results of the analysis, supervision has a positive and significant effect on Employee Work Productivity at PT. Pacific Express Cargo. This is evidenced by the significance value of the t-test statistic 0.014 < 0.050. Work Discipline has a positive and significant effect on Employee Work Productivity at PT. Pacific Express Cargo. This is evidenced by the significance value of the t-test statistic of 0.008 < 0.050. Supervision and Work Discipline have a positive and significant effect on Employee Work Productivity at PT. Pacific Express Cargo. This is evidenced by the significance value of the F statistical test 0.000 < 0.050.